Emotional intelligence matters in hospitality education: contributions of emotional intelligence, fluid ability, and personality to hospitality grades - Völker, Juliane; Blal, Inès; Mortillaro, Marcello (Frontiers in Psychology, 2023)
According to recent meta-analyses, emotional intelligence can be a meaningful predictor of academic performance. In this research, we wanted to investigate a particular group of students for which emotional intelligence should be crucial. Namely, we examined whether emotional intelligence, conceptualized as an ability, uniquely contributes to academic performance in hospitality management education beyond fluid intelligence and personality. We analyzed if fluid ability, the Big-Five personality dimensions, and ability-based emotional intelligence predict six module grades in a sample of N = 330 first-semester students at a Swiss-based hospitality school. We found that the ability to manage other people’s emotions is more predictive of module grades than fluid ability if the courses involve substantial parts of interactive work. Complementarily, the more a module involved theoretical or abstract subject material, the more fluid ability predicted performance. Other abilities and factors – emotion understanding, emotion regulation, the students’ age, conscientiousness, and openness – predicted performance only in specific modules, hinting that the didactic and grading procedures are complex and involve various skills and dispositions of the students. Given that the hospitality education and industry are buzzing with interactions with peers and guests alike, we provide evidence that interpersonal and emotional competencies are a vital part of hospitality curricula.